Industry Event Organizer Branding Strategy in Increasing Consumer Loyalty - Arwin Prayetno; Nur Insan; Muhammad Asdar (Journal La Bisecoman, 2023)
In the era of globalization and increasingly fierce business competition, branding strategy has become one of the key factors that determine the success of a company. CV. Solusi Sahabat Sejati (Sahabat Explorer Event Organizer) realizes the importance of branding in creating consumer trust and loyalty. Friends of Explore facilitate activities for educational, recreational and entertainment purposes. And committed to his field, he consistently continues to improve services, both modules and program choices, in order to meet the needs and expectations of partners who have loyally used Sahabat Explore's services. This study uses a qualitative method. suggests that qualitative methodology is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. Based on the research results above, the branding strategy for Sahabat Explorer which aims to increase consumer loyalty can involve several things: Understanding the Target Audience: with a strong understanding of who they serve, Sahabat Explorer can direct their branding efforts more effectively. Strengthening emotional connections with consumers through these values can help build stronger bonds. Consistent Brand Experience: Consistency is key in branding strategy. Explorer Friends must ensure that every touchpoint with the brand, from social media to physical products and customer service, consistently reflects their brand values and identity. By combining these strategies, Sahabat Explorer can strengthen their brand identity, deepen relationships with consumers, and increase overall consumer loyalty levels. With a holistic and consistent approach, Sahabat Explorer can build a strong and sustainable brand in the long term.